COMBINING ABILITY ESTIMATES FOR OIL CONTENT, YIELD COMPONENTS AND FIBRE QUALITY TRAITS IN COTTON (G. hirsutum) USING AN 8 × 8 DIALLEL MATING DESIGN - Sweta Alok Singh; Virendra Vikram Singh; Arvind Daulatrao Choudhary (Tropical and Subtropical Agroecosystems, 2009)
Eight cotton parental lines(CSH 7106, 3 HS, B 58-1290, 23 ES, 23 K, F 1861, VCH (F) and RS 810) were used in an 8 × 8 diallel mating design to obtain 56 F1 hybrids for combining ability analysis.. The analysis revealed significant general combining ability (GCA) and specific combining ability (SCA) effects for all the traits measured except lint index, seed index and fibre strength. Preponderance of non-additive geneaction was observed for oil content, ginning outturn, 2.5% span length and micronaire and preponderance of additive geneaction was obtained in seed yield, boll weight, fibre elongation and oil content. Significant GCA effects were observed for RS 810 for seed yield, and 2.5% span length, for 3 HS and B 58-1290 for boll weight, and CSH 7106 for oil content. Parental lines VCH (F), RS 810 and B 58-1290 were found to be a good general combiner for seed yield and parental lines CSH 7106 and VCH (F) for oil content. Some promising hybrids showing positive significant SCA effect for seed yield were 23 ES × 23 K, F 1861 × VCH (F). For oil content crosses 23 K × RS 810, B58-1290 × F1861, CSH 7106 × 23 ES and 3 HS × VCH (F) showed significant SCA effects.